Employee empowerment and job satisfaction in urban Malaysia - Idris, Aida; See, Denise; Coughlan, Paul (Emerald, 2018)
Purpose: The topic of employee empowerment and job satisfaction, and its implications for organizational change management, is underexplored in developing countries. Consequently, the purpose of this paper is to investigate the relationship between the two variables in the context of urban Malaysia as an emerging market. Differences in empowerment and job satisfaction in relation to organizational and socio-cultural environments were also assessed. The findings are then discussed in terms of their implications for organizational change management in Malaysia and other emerging countries. Design/methodology/approach: Using survey data gathered from 125 local employees working in the capital city of Kuala Lumpur, the effect of empowerment on job satisfaction was tested using correlation and regression analyses. ANOVA tests were used to determine differences in empowerment and satisfaction among sub-groups divided according to four factors in the organizational and socio-cultural environments, namely, form of ownership, job sector, type of industry and organizational hierarchy. Findings: The results demonstrate that employee empowerment has a strong positive effect on job satisfaction. However, significant differences in employee empowerment and job satisfaction between higher and lower levels of the organizational hierarchy raise concerns about organizational change diffusion and the sustainability of strategic changes. Research limitations/implications: Empirical evidences are provided for the generalizability of the theoretical link between employee empowerment and job satisfaction in the urban Malaysian context. Nevertheless, the findings have highlighted the need to further examine specific issues faced by employees in lower levels of the organizational hierarchy which affect their rates of empowerment and satisfaction in a rapidly changing environment. Practical implications: Implications on power relations between managers and their subordinates are discussed, as well as on succession and goal-sharing during periods of intense organizational change. Originality/value: By demonstrating the influence of organizational hierarchy on employee empowerment and job satisfaction in a non-western setting, this study has contributed new insights on the role of socio-culture and power relations in organizational change management.